Exploration of relations among the members of the supply chain on the basis of relationship indicators - Ványi, Noémi; Varjasi, Gergely (Acta Agraria Debreceniensis, 2014)
Today the various business units on the market are not competing individually against each other, but doing this as members of a supply chain, which are delivering the products or services to the customers with coordination. The participants are cooperating in the process of purchasing, production and sale. Their common objective is to deliver for the consumer demand. The supply chain approach of the enterprises is a business philosophy, which requires trust, commitment, coordination, shared objectives, support from the management, and the understanding and acceptance of the mutual dependence (Német, 2009). The main objective of our study is to analyse the relationships among the players of the supply chain through several relationship indicators, such as trust, economical satisfaction, social satisfaction, compelling power, non-compelling power, dependence, reputation and conflict. The relationship among the players of the supply chain has been analysed from two aspects, through the position and through the role of the players of the supply chain. This study aims to present the results of the analysis highlighting the critical points.